Performance Seismic Design of the Retrofit of a University Library using Non-Conventional Methods - Chavez, B. (2020)
This research proposes a structural retrofit of a reinforced concrete building older than 50 years. The structural system is dual using frames and walls, having an area of 1980 m2 and 4 levels with a total height of 15.50 m. There are three unconventional methods to retrofit this infrastructure. The first is to install steel jackets with bolt anchors. The second methodology is through the use of jackets and anchors of Carbon Fiber Reinforced Polymers (CFRP). The third alternative is through reinforcement of walls with 2 diagonal struts made with CFRP sheets as struts, also installing CFRP anchors at each end of both struts to ensure that these sheets work up to their high levels of tension. These anchors together with the diagonal plates contribute to give ductility to the wall and in turn resist the effects of sliding at the base, a fault that is very common in rigid structures such as walls. Each unconventional reinforcement methodology used in this research is validated using laboratory tests results of reinforced columns and walls retrofitted with every of the three innovative methods. Nonlinear static analysis - Pushover of each alternative was performed and compared with the demand for the 1974 earthquake in Lima, scaling 3 seismic records to a PGA of 0.45g, which is the acceleration of design in Lima. It is shown that these proposals are effective in providing levels of shear base and displacement capacity in the inelastic design. For the 0.40mx0.80m columns, the results show that both reinforcements increase ductility by more than 10%; on the other hand, the proposal of reinforcement in the walls of 40cm thick, produced even better results increasing ductility by 100% and shear base by 100%.